2D–2D WO3–Bi2WO6 photocatalyst with an S-scheme heterojunction for highly efficient Cr(vi) reduction. Issue 39 (21st September 2022) - Zhao, Nan-Nan; Zhang, Yi; Liu, Meng-Qi; Peng, Yin; Liu, Jin-Yun
Abstract : WO3 –Bi2 WO6 heterostructures display outstanding photo-reduction ability for high concentration of Cr(vi ) due to the formation of 2D–2D junctions and the S-scheme transfer behavior of photogenerated e–h pairs. Abstract : A two-dimensional (2D)–2D WO3 –Bi2 WO6 photocatalyst is developed by using a hydrothermal method. Ultrathin Bi2 WO6 nanosheets are grown on the surface of WO3 nanoplates by crystal-oriented epitaxy. The 2D–2D WO3 –Bi2 WO6 heterostructures display outstanding photocatalytic activity in reducing high concentrations of Cr(vi ), as a 200 mg L −1 Cr(vi ) solution can be totally degraded within 40 min. The enhanced photocatalytic performance is ascribed to the synergistic effect of the 2D–2D heterostructure between Bi2 WO6 and WO3, which provides more active sites and large surface areas, and the S-scheme transfer behavior of photogenerated electrons and holes boosts the interfacial charge separation, and retains the optimum redox ability of photo-induced charge carriers. Active radical scavenging measurements verify that h + and ˙O2 − are the main active species during the photocatalysis. These findings would inspire new opportunities for engineering emerging heterostructures with a high photocatalytic performance.